2003
DOI: 10.1034/j.1600-0714.2003.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Th1 cytokines in oral lichen planus

Abstract: These data suggest the development of a T helper 1 immune response that may promote CD8+ cytotoxic T-cell activity in OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
172
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(202 citation statements)
references
References 42 publications
15
172
0
5
Order By: Relevance
“…33,34 In the present study, all of the patients were inpatients. All of the patients and controls were instructed not to eat one hour prior to the sampling.…”
Section: Discussionmentioning
confidence: 89%
“…33,34 In the present study, all of the patients were inpatients. All of the patients and controls were instructed not to eat one hour prior to the sampling.…”
Section: Discussionmentioning
confidence: 89%
“…The pathophysiology of OLP is multifarious and in the microscopic evaluation, its features are associated with pathognomonic characteristics and degeneration of cells which is supposed to be certified to associate epithelial permeation of T-lymphocytes leading to local production of cytokines (Khan et al, 2003). Recently, it has been stated that the imbalance in levels of free radical and ROS with antioxidants may play an important role in the start of several inflammatory oral disease (Hosseini et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In various reports, it has been emphasized that IFN-γ and TNF-α are proinflammatory cytokines, that TNF-α reduces IFN-γ secretion, and that these cytokines play an active part in the clinical type and disease activity in LP. Although the findings obtained in the above-mentioned study were not compared with a control group, it has been reported that TNF-α expression increased whereas IFN-γ expression decreased [29].…”
Section: Discussionmentioning
confidence: 99%